The Association of Fecal Microbiota in Ankylosing Spondylitis Cases with C-Reactive Protein and Erythrocyte Sedimentation Rate. (7th November 2020) - Liu, Gang; Hao, Yonghong; Yang, Qiang; Deng, Shucai
Abstract : The purpose of this work was to identify the features of the gut microbiome in cases of ankylosing spondylitis (AS) testing positive for human leukocyte antigen- (HLA-) B27 and healthy controls (HCs) as well as to determine how bacterial populations were correlated with C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR). Fecal DNA extracted from fecal samples from 10 AS cases and 12 HCs was subjected to 16S rRNA gene sequencing. The two research groups did not differ significantly regarding alpha diversity. By comparison to HCs, AS cases displayed a lower relative level of Bacteroidetes (P < 0.05 ), but a higher level of Firmicutes and Verrucomicrobia (P < 0.05 ). Furthermore, the correlation between the specific gut bacteria and ESR or CRP was investigated. At the phylum level, Firmicutes and Verrucomicrobia had a positive association with ESR and CRP, while Bacteroidetes exhibited an inverse correlation with ESR and CRP. Meanwhile, in terms of genus, Bacteroides had a positive association with ESR and CRP, whereas Ruminococcus and Parasutterella had an inverse correlation with ESR and CRP, and Helicobacter also displayed an inverse correlation with CRP. Such findings indicated dissimilarities between AS cases and HCs regarding the gut microbiome, as well as the existence of correlations between bacterial populations and both ESR and CRP.